2018
DOI: 10.1161/circimaging.117.006738
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ventricular Morphology on Fiber Stress and Strain in Fontan Patients

Abstract: In comparison to Fontan patients with a dominant left ventricle, those with a dominant RV have higher fiber stress, a higher rate of ventricular dilatation, lower circumferential fiber shortening, and similar longitudinal shortening. RV morphology, ventricular dilation, and worse circumferential strain are associated with death or heart transplantation. The difference in myofiber architecture may contribute to suboptimal adaptation of the RV as a systemic ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 32 publications
7
25
1
Order By: Relevance
“…Furthermore, mechanical dyssynchrony, if not the major factor explaining early cardiac dysfunction, may impact RV function in older patients [27,28]. Finally, tricuspid regurgitation due to progressive RV dilatation contributes to worsening of ventricular function [29]. Consistently in our study, AV valve dysfunction was more common in the RV group than in the LV group.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, mechanical dyssynchrony, if not the major factor explaining early cardiac dysfunction, may impact RV function in older patients [27,28]. Finally, tricuspid regurgitation due to progressive RV dilatation contributes to worsening of ventricular function [29]. Consistently in our study, AV valve dysfunction was more common in the RV group than in the LV group.…”
Section: Discussionsupporting
confidence: 86%
“…A CMR T1 relaxometry study of pediatric Fontan patients indicated that myocardial fibrosis is present early on and has a negative influence on cardiac contractility [36]. Ghelani et al found that although Fontan patients with a right ventricular morphology had lower GCS compared with those with left ventricular morphology, their EF was similar [10], indicating that strain is a more sensitive marker for myocardial dysfunction. The fact that in the current study with relatively young Fontan patients, almost all patients had a preserved EF while strain values deteriorated, supports this theory.…”
Section: Dominant Ventriclementioning
confidence: 99%
“…Recently introduced, cardiac magnetic resonance (CMR) feature tracking offers potential qualitative advantages [7]. So far, cross-sectional studies have proven the feasibility of CMR feature tracking in the Fontan population [8,9], and have shown differences between left and right ventricular morphology [10], but serial data is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, Ghelani et al indicate that not only ventricular dilation but also a decreasing GCS are associated with worse outcome. 26 Therefore, 3D-STE, which can assess ventricular volume and strain simultaneously, may be a valuable tool for predicting the outcome of HLHS patients.…”
Section: Contribution Of Strains To Rv Function In Hlhsmentioning
confidence: 99%